Workplace Bullying in Pathology and Laboratory Medicine. Issue 4 (7th February 2023) - Chiou, Paul Z; Mulder, Lotte; Jia, Yuane
Abstract: Objectives: The specific aims of the study are to explore the prevalence of workplace bullying and to understand the impact of bullying on individual wellness in order to facilitate the development of future organizational solutions to mitigate workplace incivility. Methods: Cross-sectional data were collected via a web-based survey to gather exploratory demographic information and to assess the relationships between intensity of the exposure to the negative acts with laboratory productivity. Associations between laboratories offering resources to employees and their impacts on productivity and professional job fulfillment were also explored. Results: Results of the survey showed that over two-thirds of laboratorians (68.56%) were classified as victims of workplace bullying, and the perpetrator is most likely a peer of the victim (55.3%). The study revealed the intensity of workplace incivility was positively correlated with the number of sick days taken by the laboratory practitioner ( F (2, 217) = 24.245, P  < .001). Facilities with a supportive work environment were also associated with a reduction in the number of sick mental days taken ( P  < .001), a proxy for improved work and health outcomes. Conclusions: The results of this study shed light on the prevalence of incivility at the workplace and offer evidence on the importance of providing a supportive work environment toward reducing workplace bullying.